2019
DOI: 10.3389/fpsyg.2019.00352
|View full text |Cite
|
Sign up to set email alerts
|

The Allocation of Valenced Percepts Onto 3D Space

Abstract: Research on the metaphorical mapping of valenced concepts onto space indicates that positive, neutral, and negative concepts are mapped onto upward, midward, and downward locations, respectively. More recently, this type of research has been tested for the very first time in 3D physical space. The findings corroborate the mapping of valenced concepts onto the vertical space as described above but further show that positive and negative concepts are placed close to and away from the body; neutral concepts are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
1
8
0
2
Order By: Relevance
“…Nevertheless, the compatibility between these seemingly unrelated features (tastes and spatial locations) reflects some level of organization taking place within our conceptual system. In this case, and based on the ideas that people represent valenced concepts in 2D and 3D space (Marmolejo-Ramos et al, 2018), and that sweet and bitter are characteristically valenced stimuli, or concepts (Mennella, 2014), it is possible that, all other things being equal, participants might guide their judgements based on the feature's valence 4 . As mentioned in the introduction section, it is known that perceptual dimensions differentiate valence, something that might as well guide the extent to which people relate them to one another (Cavanaugh, MacInnis, & Weiss, 2015, Collier, 1996Velasco et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the compatibility between these seemingly unrelated features (tastes and spatial locations) reflects some level of organization taking place within our conceptual system. In this case, and based on the ideas that people represent valenced concepts in 2D and 3D space (Marmolejo-Ramos et al, 2018), and that sweet and bitter are characteristically valenced stimuli, or concepts (Mennella, 2014), it is possible that, all other things being equal, participants might guide their judgements based on the feature's valence 4 . As mentioned in the introduction section, it is known that perceptual dimensions differentiate valence, something that might as well guide the extent to which people relate them to one another (Cavanaugh, MacInnis, & Weiss, 2015, Collier, 1996Velasco et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the research also shows that people represent affective stimuli spatially, in particular, along the vertical plane, such that positively-valenced objects and words tend to be located higher relative to their negatively-valenced counterparts (e.g., Damjanovic & Santiago, 2016;Machiels & Orth, 2017;Marmolejo-Ramos et al, 2013Meier & Robinson, 2004;Sasaki, Yamada, & Miura, 2016). Moreover, in a recent study, Marmolejo-Ramos et al (2018) provided some evidence for the idea that in terms of 3D space, participants consistently place positive (negative) concepts in higher (lower) locations and nearer to (farther from) their body (see also Piqueras-Fiszman, Kraus, & Spence, 2014) with no preferential associations with locations in the horizontal plane (though note that previous research has, on occasion, documented a weaker pitch/left-right association, see Mudd, 1963).…”
Section: Introductionmentioning
confidence: 92%
“…In particular, there is a general bodily tendency to approach positive and avoid negative cues and do so faster than vice versa (20). Moreover, it was shown that positive concepts and percepts are placed closeto-the-body locations, while negative concepts and percepts are placed away-from-the-body locations (21,22). This gives evidence for a general bodily reaction to positive or negative stimuli (20,23).…”
Section: Introductionmentioning
confidence: 94%
“…In particular, there is a general bodily tendency to approach positive and avoid negative cues and do so faster than vice versa (Phaf et al, 2014 ). Moreover, it was shown that positive concepts and percepts are placed close-to-the-body locations, while negative concepts and percepts are placed away-from-the-body locations (Marmolejo-Ramos et al, 2018 , 2019 ). This gives evidence for a general bodily reaction to positive or negative stimuli (Phaf et al, 2014 ; Sharbanee et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%